2016
DOI: 10.1016/j.jvs.2016.03.454
|View full text |Cite
|
Sign up to set email alerts
|

Aortic outflow occlusion predicts rupture of abdominal aortic aneurysm

Abstract: We demonstrate that AOO, PAD, and COPD in AAA are associated with rAAAs at smaller diameters. AOO appears to increase PWS, whereas COPD and PAD may be surrogate markers of decreased aortic wall strength. We therefore recommend consideration of early, elective AAA repair in patients with AOO, PAD, or COPD to minimize risk of early rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…20 Vollmar et al reported a 5.1 fold higher prevalence of AAA in World War II amputees versus nonamputated veterans, speculating on aneurysm bulging and appositional luminal thrombus, 21 whereas Crawford et al reported AAA rupture depending on aortic outlfow. 16 With the flow modulated PPE, it has been shown in the present study that mimicking impaired aortic outflow by iliac or distal aortic stenosis increases AAA diameter significantly, with aneurysms bulging to the contralateral side, and has different effects on the circumference of the aortic wall (Fig. 2B).…”
Section: Discussionsupporting
confidence: 51%
“…20 Vollmar et al reported a 5.1 fold higher prevalence of AAA in World War II amputees versus nonamputated veterans, speculating on aneurysm bulging and appositional luminal thrombus, 21 whereas Crawford et al reported AAA rupture depending on aortic outlfow. 16 With the flow modulated PPE, it has been shown in the present study that mimicking impaired aortic outflow by iliac or distal aortic stenosis increases AAA diameter significantly, with aneurysms bulging to the contralateral side, and has different effects on the circumference of the aortic wall (Fig. 2B).…”
Section: Discussionsupporting
confidence: 51%
“…We have previously identified peripheral arterial disease and aortic outflow occlusion as surrogate markers for increased PWS, decreased aortic wall strength, and features of early AAA rupture. 20 Our objective in this study was to explore the association between ILT and risk of AAA rupture, particularly in small aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…1), the degree and direction of bulging of the aneurysm from the natural curvature of the infrarenal aorta, the angle of the iliac bifurcation, and the presence of an extra renal artery (which manifests in approximately one third of all cases) 20 could be considered. There is similarly a need to consider possible effects of peripheral vessel disease, such as stenosis or occlusion, and effects of spinal cord injury or lower limb amputation, all of which can adversely affect AAA hemodynamics 2123 . Such simulations were simply beyond the present scope, particularly noting that one would need to appropriately adjust outlet conditions to account for remodeling of the contralateral iliac/femoral in cases of unilateral disease or amputation, hence increasing the parametric space considerably.…”
Section: Discussionmentioning
confidence: 99%